Connected autonomous driving using reconfigurable intelligent metasurfaces - Lestas, Marios; Ehizogie, Emoyon-Iredia; Saeed, Taqwa; Ashraf, Nouman; Liaskos, Christos; Segata, Michele; Paolo, Casari; Aduard, Alarcon; Pitsillides, Andreas (My University, 2024)
Beyond 5G/6G communication systems promise to significantly impact the development of a New Generation of CCAM. Reconfigurable Intelligent Metasurfaces (RIM) are by now established as a key enabling technology for 6G Systems. They have been extensively investigated the last few years, as they possess exotic properties allowing for precise control over any aspect of an impinging wave. As such, they can be harnessed for the realization of Programmable Wireless Environments (PWE). Despite their investigation for deployment in a number of applications, their integration in Connected Autonomous Driving Applications has not been considered in literature with respect to cooperative driving performance. In this chapter, we consider the HyperSurface (HSF) as the enabling technology for RIM and present recent results demonstrating the feasibility and the associated performance gains achieved from the integration of RIM in Connected Automated Driving Applications. We discuss HSF design considerations which can affect CCAM performance with respect to the system architecture, the controller network and the associated routing protocols, the workload characterization and the closed loop beam steering design. We envision the chapter to serve as a synopsis of tools and methodologies that can be used for RIM-enabled CCAM system design.
Keywords: Vehicular Comunications; Metasurfaces